2014
DOI: 10.3109/08820139.2014.942459
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effects of Ethanolic Extract fromSargassum horneri(Turner) C. Agardh on Lipopolysaccharide-Stimulated Macrophage ActivationviaNF-κB Pathway Regulation

Abstract: Inflammation is major symptom of the innate immune response by infection of microbes. Macrophages, one of immune response related cells, play a role in inflammatory response. Recent studies reported that various natural products can regulate the activation of immune cells such as macrophage. Sargassum horneri (Turner) C. Agardh is one of brown algae. Recently, various seaweeds including brown algae have antioxidant and anti-inflammatory effects. However, anti-inflammatory effects of Sargassum horneri (Turner) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…Macrophages are one of the major cell types in immune cells, and they play a role in the inflammatory immune response (Kim et al ., ). In our study, TFDG regulated the activation of macrophages: low doses suppressed the production of pro‐inflammatory cytokines, including IL‐6, IL‐12, IFN‐γ and TNF‐α, while high doses exhibited weak upregulation (Couturier et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are one of the major cell types in immune cells, and they play a role in the inflammatory immune response (Kim et al ., ). In our study, TFDG regulated the activation of macrophages: low doses suppressed the production of pro‐inflammatory cytokines, including IL‐6, IL‐12, IFN‐γ and TNF‐α, while high doses exhibited weak upregulation (Couturier et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Activated NF-κB is involved in immune regulation, inflammatory response, cell growth, and antiapoptosis via phosphorylating IκB and shifting into the nucleus [40][41][42]. Notably, previous studies have shown that the suppression of NF-κB pathway is associated with anti-inflammatory responses [43][44][45][46]. Therefore, we explored whether GEA could regulate NF-κB signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous studies, both seaweed species are rich in antiinflammatory compounds. Especially, phlorotannins separated from EC (2,7-phloroglucinol-6, phloroglucinol, eckol, pyrogallol-phloroglucinol-6,6-bieckol, dieckol, and 6-bieckol), and sulfated polysaccharides and crude extracts separated from SH found to possess promising anti-inflammatory effects under in vitro and in vivo conditions (Lee et al 2014b, Kim et al 2015. Moreover, both seaweeds are considering as important, medicinal ingredient in traditional medicine (15.6-250 μg mL -1 ) for 24 h. Then, MTT was added (200 μg per well) to each well.…”
Section: Chemicals and Regentsmentioning
confidence: 99%